Mental Health and Acculturation in Asian American Families - Trinh, N.-h. (Springer, 2017)
Asian Americans are the fastest growing minority group in the United States. When Asian immigrants arrive in the United States, they regularly encounter a vast number of difficulties integrating themselves into their new culture. In Handbook of Mental Health and Acculturation in Asian American Families, distinguished researchers and clinicians discuss the process of acculturation for individuals and their families, addressing the mental health needs of Asian Americans and thoroughly examining the acculturative process, its common stressors, and characteristics associated with resiliency. This first-of-its-kind, multi-dimensional title synthesizes current acculturation research, while presenting those concepts within a clinical framework. In addition to providing an in-depth look at both past and present research and offering directions for future topics to explore, the book also offers a range of practical tools such as research scales to measure levels of acculturation, interview techniques, and clinical approaches for special populations including children, the elderly, and their families. Thought-provoking and informative, Handbook of Mental Health and Acculturation in Asian American Families will enhance the understanding of the clinical and sociocultural problems Asian Americans face, providing clinicians with all the necessary insights to better care for their patients.